2019
DOI: 10.1111/aen.12436
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance status of Bemisia tabaci MEAM1 (Hemiptera: Aleyrodidae) in Australian cotton production valleys

Abstract: The whitefly Bemisia tabaci Middle East‐Asia Minor 1 (MEAM1), previously known as B biotype, is a major agricultural pest with a reputation for developing resistance to insecticides. DNA‐based identification revealed that B. tabaci MEAM1 is the dominant species within Australian cotton cropping. Discriminating doses of 10 mg/L for pyriproxyfen and 300 mg/L for both diafenthiuron and bifenthrin were determined from bioassay data collected in 2010–2015. Resistance to these insecticides was tested in whitefly pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 61 publications
3
35
0
Order By: Relevance
“…While the vector responsible for the spread of the CMD in South-East Asia is not well-understood, the pandemic in east and central Africa was associated with the distribution of sub-Saharan African (SSA) species of the Bemisia whitefly complex 13 . Invasive whitefly species such as the Mediterranean (MED), Middle East-Asia Minor 1 (MEAM1), and SSA2, have become pests of global agriculture, spreading plant viral diseases and becoming resistant to chemical control agents 18 , 19 . In particular, the endemic African cassava Bemisia whitefly SSA2 species occupies regions affected by the CMD pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…While the vector responsible for the spread of the CMD in South-East Asia is not well-understood, the pandemic in east and central Africa was associated with the distribution of sub-Saharan African (SSA) species of the Bemisia whitefly complex 13 . Invasive whitefly species such as the Mediterranean (MED), Middle East-Asia Minor 1 (MEAM1), and SSA2, have become pests of global agriculture, spreading plant viral diseases and becoming resistant to chemical control agents 18 , 19 . In particular, the endemic African cassava Bemisia whitefly SSA2 species occupies regions affected by the CMD pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown a trend of increasing insect resistance against conventional chemical insecticides 51,52 . Presently, no studies have been published regarding the evolution of resistance in hemipteran pests toward RNAi; however, evolution of resistance to dsRNA in the coleopteran insect, Western corn rootworm, D. virgifera virgifera , recently has been shown experimentally 53 …”
Section: Development Of Rnai‐based Products For Hemipteran Pest Controlmentioning
confidence: 99%
“…Both nymphs and adults can also secrete honeydew, which can induce coal pollution. Besides B biotype (MEAM1) is the dominant species which signi cantly threatened many agricultural commodities in numerous countries [4][5][6] . Moreover, for the excessive use of synthetic pesticides have contributed to resistance development of B. tabaci.…”
Section: Introductionmentioning
confidence: 99%
“…39 (d, J = 9.3 Hz, 1H, NH), 5.59 (m, 1H, H-5), 5.50 (d, J = 5.2 Hz, 1H, OH-2'), 5.40 (dd, J = 15.4, 6.8 Hz, 1H, H-4), 5.09 (d, J = 6.6 Hz, 1H, H-8) , 4.96 (d, J = 4.1 Hz, 1H, OH-3), 4.93 (d, J = 5.5 Hz, 1H, OH-3''),4.90 (dd, J = 7.9, 5.0 Hz, 2H, OH-2'' , OH-4''),4.51 (t, J = 5.9 Hz, 1H, OH-6''), 4.12 (d, J = 7.8 Hz, 1H, H-1''), 3.99 (dd, J = 12.9, 6.6 Hz, 1H, H-1), 3.92 (dd, J = 10.4, 5.8 Hz, 1H, H-3), 3.81 (m, 2H, H-2, H-2'), 3.66 (dd, J = 10.0, 6.1 Hz, 1H, H-6''), 3.52 (dd, J = 10.3, 3.7 Hz, 1H, H-1), 3.43 (dt, J = 11.7, 5.9 Hz, 1H, H-6''),3.13 (td, J = 8.8, 4.8 Hz, 1H, H-3''), 3.08 (d, J = 5.8 Hz, 1H, H-5''), 3.04 (dd, J = 8.8, 5.2 Hz, H, H-4'') , 2.95 (td, J = 8.4, 4.2 Hz, 1H, H-2''), 1.98 (m, 4H, H-6, H-7), 1.92 (t, J = 7.5 Hz, 2H, H-10), 1.55 (d, J = 14.5 Hz, 3H, Me-9), 1.47 -1.14 (overlap, m, 40H, CH 2 -11~17, CH 2 -3'~15') , 0.86 (s, m, 6H, Me-18, Me-16'). 13 C NMR (151 MHz, DMSO) δ 174.14 (C-1'), 135.26 (C-9), 131.47 (C-5), 131.39 (C-4), 123.86 (C-8), 103.89 (C-1''), 77.28 (C-5''), 76.93 (C-3''), 73.78 (C-2''), 71.41 (C-2'), 70.93 (C-1), 70.39 (C-4''), 69.11 (C-3), 61.44 (C-6''), 53.22 (C-2), 39.43 (C-10) 34.86 (C-3'), 32.54 (C-6), 31.69 -29.07 (overlap, C-12~16, C-5'~14'), 27.75 (C-7), 27.62 (C-11), 24.92 (C-4'), 22.49 (C-15'), 16.09 (C-19), 14.31 (overlap, C-18, C-16').…”
mentioning
confidence: 99%